Imagens sedutoras da cidade: uma arqueologia das marcas imagéticas na produção do espaço urbano em Campina Grande/PB - Araujo, José Arimatéia da Silva (2019)
The research work proposed in this thesis sought to investigate the wills of truth in the constitution of seductive images of the city of Campina Grande as a hyperbolic city, reflecting on the construction and circulation of meanings predominant in the process of urban (re) production of Campina Grande and its symbolic marks. From the mediation between the discursive formations, the journalistic discourse was taken, especially from the editorials of the newspapers Diário da Borborema and Jornal da Paraíba for the constitution of the corpus of analysis of this research. It started from the question of how the spatial practices of Campina Grande's political-commercial elite forged symbolic images of the city, on multiple spatial scales, claiming state actions based on memory and the reactivation of meaning effects as forms of sayability and real effects. Thus, the discursive discussions were linked to the production of the urban space of the state, since as can be observed in Lefebvre, the urban space is a result of the condition of social practice. To this end, studies using French Discourse Analysis were used, based mainly on the contributions of Foucault (1997; 1999 and 2008), Orlandi (1998 and 2002), Michel Pêcheux (1997 and 1999) between others who assisted in discussions about the concepts of discourse, interdiscourse, discursive formations, discursive memory and event. Moreover, such discussions were linked to those inherent in the production of space. In this sense, Lefèbvre (2006; 2008 and 2010), Raffestin (1993), Corrêa (2013), among others whose productions on this theme are very expensive, guided the analysis. In this perspective, we present interdisciplinary discussions that led to the understanding of the spatial production of the city of Campina Grande, as a result of discursive practices for the constitution of the hyperbolic city.